2014
DOI: 10.11118/actaun200957040125
|View full text |Cite
|
Sign up to set email alerts
|

Relation between some climate parameters inside and outside the stable in the course of the year

Abstract: The objective of the present study was to evaluate the relation between some climate parameters inside and outside the stable in the course of the year. Investigations were carried out from 1 July 2007 to 30 June 2008 at the School Farm in Žabčice. We monitored the following micro-climate pa­ra­me­ters: temperature (°C), relative humidity (%) and the temperature-humidity index (THI) inside and outside the stable. We used the statistical programme UNISTAT version 5.1.11 to calculate the average monthly temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 4 publications
1
3
0
Order By: Relevance
“…Values of average diurnal temperatures calculated in individual seasons corresponded in essence to those mentioned in a study by Walterová et al (2009) and documented also the absence of extreme climatic changes in the course of this experiment. The value of summer average diurnal temperature indicated that the limit of heat stress could be overpassed on some days in this season (Kadzere et al, 2002;Brouček et al, 2006;Hanuš et al, 2008).…”
Section: Resultssupporting
confidence: 80%
“…Values of average diurnal temperatures calculated in individual seasons corresponded in essence to those mentioned in a study by Walterová et al (2009) and documented also the absence of extreme climatic changes in the course of this experiment. The value of summer average diurnal temperature indicated that the limit of heat stress could be overpassed on some days in this season (Kadzere et al, 2002;Brouček et al, 2006;Hanuš et al, 2008).…”
Section: Resultssupporting
confidence: 80%
“…The farm is situated in the village of Žabčice in a lowland area (GPS 49°0'51.786"N, 16°36'14.809"E) at the altitude of 179 m. All cows were kept together under identical conditions in a loose housing system with bedding and received a complete feeding ration ad libitum. Cows were milked twice a day at 4.00 and 16.00 h. This was the same barn as that used in experiments performed by Walterová et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…According to Bouraoui (2002) the milk performance is a function of THI: with increasing values of THI milk yields decrease and in the zone above 69 each unit change in THI causes a decrease in milk yield by 0.41 kg per head and day. It results from studies performed by Erbez et al (2010) and Walterová et al, (2009) that under Central European conditions high values of THI are predominantly influenced by high temperatures and that the effect of relative air humidity is substantially lower. The above authors observed in their studies that during hot summer months the values of relative air humidity were lower while in winter they were much higher.…”
mentioning
confidence: 99%
“…al., 2007). The rank of lactation also plays a certain role because Walterová et al (2008) observed that the average barn airspace temperature of 22 °C already stressed dairy cows on the second lactation while in older animals the trigger of stress were temperatures above 25 °C.…”
mentioning
confidence: 99%